Prolonged Standing Strain Index (PSSI): A Proposed Method to Quantify Risk Level of Standing Jobs in Industrial Workplaces - Isa, Halim (2011)
Industrial occupations such as metal stamping workers, electronics parts assembly operators, automotive industry welders, and lathe operators perform their jobs in standing position for a long period of time. Prolonged standing can contribute to discomfort, and muscle fatigue particularly in the back and legs. This study developed prolonged standing strain index (PSSI) to quantify risk levels due to standing jobs and propose recommendations to minimize the risk levels. Risk factors associated with standing jobs such as working posture, muscles activity, standing duration, holding time, whole-body vibration, and indoor air quality were considered as basis to develop the PSSI. All risk factors are assigned with multipliers, and the PSSI is the product of these multipliers. Based on PSSI, recommendations were proposed, however, extensive studies are required to validate their effectiveness.